2021
DOI: 10.1016/j.optom.2020.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The association between nearwork-induced transient myopia and progression of refractive error: A 3-year cohort report from Beijing Myopia Progression Study

Abstract: Purpose To investigate the natural change of nearwork-induced transient myopia (NITM), and its association with the progression of refractive error. Methods Students of the Beijing Myopia Progression Study were examined at baseline and follow-up examinations, which included cycloplegic autorefraction. Initial NITM and its decay were assessed objectively immediately after binocularly-viewing and performing a sustained 5-minute near task (20 cm). Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
(8 reference statements)
0
1
1
1
Order By: Relevance
“…A 3-year cohort report suggested that there were 142 myopic (63.7%) students from Beijing Myopia Progression Study. Their myopia rate was higher than that of grades 5–6 in our study [ 29 ]. Nevertheless, some countries have low prevalence rates, such as Brazil of3.14% and Saudi Arabia of 0.7% [ 30 , 31 ].…”
Section: Discussioncontrasting
confidence: 68%
“…A 3-year cohort report suggested that there were 142 myopic (63.7%) students from Beijing Myopia Progression Study. Their myopia rate was higher than that of grades 5–6 in our study [ 29 ]. Nevertheless, some countries have low prevalence rates, such as Brazil of3.14% and Saudi Arabia of 0.7% [ 30 , 31 ].…”
Section: Discussioncontrasting
confidence: 68%
“…Its magnitude is also related to the risk of myopia progression. 12 , 31 Our results showed that the degree of myopia increased by 0.19 ± 0.23 D after 4 hours of reading in the textbook group, which was close to the results of Sivaraman et al (0.26 ± 0.12 D). 32 The main factor contributing to NITM is indeed fatigue in the accommodation system caused by prolonged nearwork.…”
Section: Discussionsupporting
confidence: 90%
“… 11 17 An article investigating the association between near work-induced transient myopia (NITM) and progression of refractive error found that there was more relative myopic refractive progression for hyperopic children with more NITM. 17 The authors inferred that it might be through a mild spasm of the ciliary and increased variability of NITM decay response, which meant the hyperopic children with more NITM had inaccurate accommodative function. A previous study by Kang et al reported that pseudomyopia was not associated with the progression of myopia.…”
Section: Discussionmentioning
confidence: 99%